2023
DOI: 10.1177/19458924231157619
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study in Immune Response of BALB/c and C57BL/6 Mice with a Locally Allergic Rhinitis Model

Abstract: Background BALB/c and C57BL/6 mouse strains are commonly used in allergy research. The current study investigated the immunological differences between these two mouse strains with a locally allergic rhinitis model. Methods Eighteen BALB/c and eighteen C57BL/6 mice received different doses of ovalbumin (OVA) intranasally for eight weeks (each mouse strain has three subgroups, 25 mg/mL group, 0.25 mg/mL group, and the PBS group). The allergic symptoms, OVA-specific serum antibody (IgE, IgG1, IgG2a), cytokines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…While we previously showed a modest neutralizing antibody response elicited by VLP-CoV-2 S2 in BALB/c mice, the dissimilarity found in this study could be attributed to the lower dose used for vaccinations (7.5 µg vs 14 µg) and the immunological differences in the mouse models (C57BL/6 vs BALB/c). 33,34 To probe the mechanistic basis of this S2-based protection, we probed a possible role for cytotoxic T cell responses. We found that mice treated with an anti-CD8 depletion antibody and immunized with VLP-CoV-1 S2 had similar virus titers in the lung compared to non-T celldepleted mice after MA10 challenge, suggesting CD8 + effector T cells do not play a vital role in S2-based protection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While we previously showed a modest neutralizing antibody response elicited by VLP-CoV-2 S2 in BALB/c mice, the dissimilarity found in this study could be attributed to the lower dose used for vaccinations (7.5 µg vs 14 µg) and the immunological differences in the mouse models (C57BL/6 vs BALB/c). 33,34 To probe the mechanistic basis of this S2-based protection, we probed a possible role for cytotoxic T cell responses. We found that mice treated with an anti-CD8 depletion antibody and immunized with VLP-CoV-1 S2 had similar virus titers in the lung compared to non-T celldepleted mice after MA10 challenge, suggesting CD8 + effector T cells do not play a vital role in S2-based protection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Balb/c mice have strong Th2 immune response, a common response in allergic reactions and infectious diseases, high production of IgG1 and IgA, high complement activity, and low interferon production. Additionally, Balb/c mice produce stronger humoral response against antigens in comparison with C57BL/6 strain ( Bleul et al, 2021 ; Aoki et al, 2019 ; Zhang et al, 2023 ; Laurenti et al, 2004 ; Kuroda et al, 2002 ; Koo and Gan, 2006 ; Watanabe et al, 2004 ).
Fig.
…”
Section: Animal Models Of CImentioning
confidence: 99%
“…C-Kit is the receptor for the MC growth factor SCF [28,29]. Various rodent laboratory strains, including BALB/c, C57BL/6J, NC/Nga, ICR mice, and Sprague-Dawley rats, are used for the study of allergic diseases through specific treatments [30][31][32]. The generation of distinct allergy models by specific treatment and stimulation of animal models is listed in Table 2.…”
Section: Introductionmentioning
confidence: 99%